PHYSIOLOGICAL ASPECTS OF IN VITRO-GROWN COCONUT (Cocos nucifera L.) PLANTS DURING ACCLIMATIZATION - C S Ranasinghe; L K Weerakoon; Y M H Liyanage; D T Mathes (International Coconut Community Journal, 1999)
The physiological status of in vitro-grown coconut (Cocos nucifera L.) plants during acclimatization was studied using nursery-raised seedlings as the control. The percentage of open stomata in leaves of in vitro-grown coconut plants was high at the initial stage of acclimatization but decreased during the course of acclimatization indicating an improvement in stomatal regulation. A progressive increase in the stomatal density, epicuticular wax deposition and leaf thickness in in vitro-grown plants was observed during acclimatization. As a result of the low light intensity, the epidermal cells of in vitro-grown plants were narrower and longer when compared to the control. With the exposure of plants to increased light intensity, the cells became wider and shorter as observed in the control. The leaf chlorophyll content was high in in vitro-grown plants under low light intensity. With increasing light intensity, a reduction in leaf chlorophyll content in vitro-grown plants was observed and at the later stages of acclimatization, it was comparable to that of the control. Variations in the rates of photosynthesis and transpiration in vitro-grown plants were observed in response to the changing environmental conditions. However, at the end of acclimatization, where the plants were ready to be transferred to the field, the physiological statuses of in vitro-grown coconut plants were comparable to that of nursery raised seedlings. The present study revealed that the embryo-cultured coconut plants could adjust well to the changing environmental conditions during acclimatization.